PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PADA MATA PELAJARAN IPA MATERI BAGIAN-BAGIAN BUMI KELAS V DI SD MUHAMMADIYAH PURWODADI - Tiara Dwi Damayanti; Suyoto; Nur Ngazizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to produce a product in the form of monopoly learning media in the subject of science, the material of parts of the earth for grade V at SD Muhammadiyah Purwodadi and to determine the feasibility of the product developed. This study uses a research and development method (Research and Development) using the ADDIE development model which consists of 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. The study was conducted at SD Muhammadiyah Purwodadi with the research subjects of grade V Al-Mu'min students of SD Muhammadiyah Purwodadi in the 2024/2025 academic year totaling 26 students. Data collection techniques or instruments used were observation, interviews, questionnaires, and tests. The test instrument consisted of a pretest and posttest which were used to determine the effectiveness of the product. The data analysis used was feasibility analysis, practicality analysis, and effectiveness analysis. The results of this study are: 1) Producing a product in the form of Monopoly Learning Media in the Subject of Science, the Material of Parts of the Earth for Grade V at SD Muhammadiyah Purwodadi; 2) Product feasibility includes validity, practicality and effectiveness, namely: a) Product validity obtained an average percentage of 92.5% with the criteria of "very feasible". Product practicality obtained an average percentage of 85.96% with the criteria of "very practical". Effectiveness obtained an average percentage of 73.15% with the criteria of "effective".